Polyhydramnios and its relation to birth defects. - San Martín, José (2015)
Retrospective study of 1033 ultrasound examinations done at Cayetano Heredia National Hospital during 28 months to evaluate the relationship between the diagnosis of polihydramnios done in 20% (9/45) of newborns with any congenital anomaly was significatively greater than that found in 0,81% (8/988) of normal newborns (p < 0,001). Fifty-three percent of pregnancies with polyhydramnios was associated with a newborn with any congenital anomaly. This suggest that any pregnancy complicated with polihydramnios needs a careful ultrasound examination to discard congenital anomalies.